THE CORRELATION BETWEEN STUDENTS’ PERCEPTION ON GERAKAN LITERASI SEKOLAH AND STUDENTS’ READING ENGLISH ACHIEVEMENT OF SMAN 4 KEDIRI - Fadhila, Madarina; Putri, Kristanti Yuntoro; Asyhar, Wildan Isna (Jurnal Pendidikan Bahasa Inggris Proficiency, 2023)
This research aims to describe and analyze: (1) to find out students’ perception of the program Gerakan Literasi Sekolah, (2) to find out the reading English achievement of students’, (3) to find out the correlation between Gerakan Literasi Sekolah and students’ reading English achievement at SMAN 4 Kediri. This research used the quantitative approach as the research design. Then, the data collected by using questionnaire and document. This research carried out 194 students of eleventh grade of SMAN 4 Kediri as the sample. The result showed that: (1) the results of the students' perceptions of the Gerakan Literasi Sekolah took a sample of 194 students. The questionnaire consists of 20 questions, with a total of 3.880 answers. Data analysis of the average number of students answered "yes" a total of 3.578, answered "no" a total of 302. So, from the result it can have a positive impact on students' reading desire. (2) the result of student reading English achievement shows a total of 194 students. A minimum student score of 75 with a total of 2 students or 1.0% and a maximum student score of 92 with a total of 1 student or 0.5. The average score of the dominant students is 83 with a total of 65 students or 33.5%. So, from the result can the score of students reading English is positive with good results. (3) the result of the students' perceptions of the Gerakan Literasi Sekolah on students' reading English achievement have a significant effect 0.031 < 0.05 on the t-test. So, from the result can be concluded that Ha is accepted.